Feeding corn germ instead of corn grain on the performance of Holstein dairy cows fed low-forage diet and human-edible feed conversion efficiency - A. Noormohammadi; G.R. Ghorbani; M. Alikhani; A. Sadeghi-Sefidmazgi; H. Rafiee; J.K. Drackley (Animal, 2022)
Using corn germ (CG) instead of corn grain could maintain dairy cow performance and might increase the efficiency of human food production. The primary objective of this study was to evaluate the effects of replacing corn grain with CG on the performance, nutrient intake, and digestibility of dairy cows. It also aimed to investigate the effect of CG on the efficiency of human food production in high-producing Holstein dairy cows in early lactation. Nine multiparous Holstein cows with 65.6 ± 8.5 DIM, milk yield of 55.6 ± 4.5 kg/d, and body weight of 611.3 ± 43.3 kg (mean ± SD) were used in a 3 × 3 Latin square design with 21-d periods. Treatments were (1) control treatment (CT, diet contains corn grain), (2) alternative treatment (AT, diet where corn grain was replaced with CG), and (3) balanced treatment (BT, diet where corn grain was replaced with CG but with the same energy content as CT). Control and balanced diets were isoenergetic (6.61 MJ/kg of DM); however, AT had higher energy (6.77 MJ/kg of DM). Treatments had no effect on dry and organic matter intake. NDF intake, however, was higher in CG diets compared with CT (P = 0.0001). Total-tract digestibility of DM tended to be reduced (P = 0.08), and OM digestibility was reduced (P = 0.05) by the inclusion of CG in diets. Whole and energy-corrected milk production were greater in AT compared with CT and BT (P < 0.05). Milk yield was similar in cows fed CT and BT. Treatments had no effect on milk composition or feed efficiency. Diet CT, when compared with CG diets, had lower efficiency in terms of human-edible feed conversion efficiency (HeFCE) and net food production (P < 0.05). Diet BT had greater HeFCE and net production of human-edible CP than AT (P < 0.05). Plasma BHBA, non-esterified fatty acids, and glucose concentrations were not affected by treatments, but plasma cholesterol was higher in cows that consumed CG diets (P = 0.04). The results indicate that, in high-producing early lactation dairy cows fed high concentrate diets, net food protein production can be substantially improved without lowering milk production through the reduction of dietary starch from 30.2 to 24.8% by replacing corn grain with CG.